Hak Dan Kewajiban Masyarakat Desa Terhadap Tanah Adat Oleh Krama Desa Adat Tamblang , Kecamatan Kubutambahan, Kabupaten Buleleng - I Dewa Made Sasrawan; Ida Bagus Anggapurana Pidada (Lembaga Pengembangan Kinerja Dosen, 2024)
Most of the people of Tamblang Village have a livelihood as farmers. So that the thick ancestral traditions and culture are still carried out intact in this village. Tamblang is a village located in the Kubutambahan sub-district, Buleleng Regency, Bali Province, Indonesia. Customary laws or awig-awig are still the basis for behavior in the community. Regulations regarding the existence and rights of customary law communities regarding customary land in Tamblang Village are one of them in Awig-Awig Tamblang Traditional Village, Kubutambahan District, which shows that the existence and rights of indigenous peoples have been accepted within the legal framework applicable in traditional villages. The Tamblang customary law community is the indigenous people of North Bali who have lived for generations based on local cultural wisdom. Customary laws or awig-awig are still the basis for behavior in society. This arrangement of rights and obligations towards customary land is the basis for community engagement by the residents of the Tamblang customary village. The purpose of this study is to know and understand the existence of awig-awig and perarem in the regulation of customary land rights and obligations. The author uses an empirical research method using an approach through laws and conceptual methods. The results of this study can be concluded that, it is expected to maintain, maintain, and maintain customary law values. This regulation certainly gives hope to customary law communities to get recognition and protection of their rights, namely customary territories, customary law, assets and/or customary objects as well as institutions/government systems.